Evaluation of corneal morphology, pupillometry, and ocular surface parameters in Fabry disease patients: correlation with plasma Lyso-Gb3 levels - Dal, Ali; Kutluksaman, Bunyamin; Akikol, Talip; Erdag, Murat; Canleblebici, Mehmet; Turgut, Faruk Hilmi (Springer, 2026)
Background Fabry disease is an X-linked lysosomal storage disorder characterized by systemic glycosphingolipid accumulation that may disrupt endothelial and neuronal integrity, leading to autonomic and ocular involvement. Non-invasive ocular imaging may offer early diagnostic biomarkers reflecting systemic disease activity. This study aimed to evaluate autonomic, ocular surface, and corneal morphological parameters in patients with Fabry disease (FD) and explore their correlations with plasma Lyso-Gb3 concentrations. Methods In this prospective cross-sectional study, 25 eyes of genetically confirmed FD patients and 25 age-and sex-matched healthy controls were examined. All participants underwent dynamic pupillometry, non-contact tear break-up time, Schirmer I testing, meibography, and anterior-segment optical coherence tomography (AS-OCT) to quantify corneal epithelial thickness. Plasma Lyso-Gb3 levels were available for 14 patients. Group comparisons were performed using Mann-Whitney U and t-tests, and correlations were assessed via Spearman analysis. Results Static pupil diameters were wider in Fabry patients under all light conditions, though not significantly (p > 0.05). Maximal Redilation Velocity (MRV) was significantly reduced in patients with FD (p = 0.015), possibly indicating sympathetic dysfunction. Peripheral (5-7 mm) corneal epithelial thickness was significantly thinner in patients with FD (p = 0.031). Lyso-Gb3 concentrations exhibited moderate, statistically significant negative correlations with epithelial thickness across all zones (central r = - 0.659, paracentral r = - 0.638, peripheral r = - 0.607; all p < 0.05). No significant associations were found between Lyso-Gb3 and pupillometric or ocular-surface parameters (p > 0.05). Conclusion Fabry disease involves subclinical ocular autonomic and structural alterations, reflected by reduced MRV and peripheral epithelial thinning correlated with biochemical disease load. Dynamic pupillometry and AS-OCT-based epithelial mapping may serve as complementary, non-invasive biomarkers for early diagnosis and monitoring of Fabry-related ocular involvement.
Keywords: Fabry Disease; Dynamic Pupillometry; Corneal Epithelial Thickness; Lyso-Gb3